Intracranial Arachnoid Cysts in Childhood: Pathogenesis, Clinical Features, and Management - Franklin Bernardes Faraj de Lima; Tancredo Alcântara Ferreira Júnior; Laryssa Crystinne Azevedo Almeida; Lano de Sousa Moreira; Hian Penna Gavazza Figueiredo; Marcos Dellaretti; Bruno Silva Costa (Brazilian Society for Pediatric Neurosurgery, 2022)
Arachnoid cysts are mostly incidental congenital lesions. Although commonly asymptomatic, it may present with nonspecific symptoms, such as headache, epilepsy, and signs of high intracranial pressure. In cases when symptoms are evident, surgical treatment has more precise indication, but the modalities and criteria for treatment remain controversial in the literature. All this makes arachnoid cysts a challenging topic in neurosurgery, raising discussions about diagnosis, management, and prognosis. This review aimed to present, in a didactic and straightforward way, already established knowledge and more recent updates, clarifying key points to guide the management and therapeutic decision of intracranial arachnoid cysts.